Coronary Aneurysm: An Enigma Wrapped in a Mystery - Carino, Davide; Agarwal, Arvind; Singh, Mrinal; Meadows, Judith; Ziganshin, Bulat A.; Elefteriades, John A. (AORTA, 2019)
Coronary aneurysms are defined as localized dilatations of the coronary arteries. In this review, we will analyze the most important aspects of this rare condition while trying to provide answers to the following questions: What is a coronary aneurysm? What causes coronary aneurysm? Do coronary aneurysms cause symptoms? Can coronary aneurysms rupture? How do we treat coronary aneurysms?
Keywords: coronary artery aneurysm; coronary aneurysm; aneurysm